Studying CO₂ conversion in DC glow discharge - Lisovskiy, V.A.; Dudin, S.V.; Platonov, P.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2020)
We have registered the mass-spectra of the gas mixture leaving the chamber and the discharge current-voltage characteristics and determined the specific energy input (SEI), the absolute conversion coefficient χ and the conversion energy efficiency η in the CO₂ pressure range of 0.05…5 Torr. Converting CO₂ molecules was performed in the glow discharge in a chamber with distributed same-side gas supply and pumping. As a result the conversion coefficient χ equaling 70% was achieved, but the conversion energy efficiency η did not exceed 1…3% because of considerable power loss due to acceleration of positive ions, gas and electrode heating as well as to inelastic collisions between electrons and gas molecules not leading to CO₂ conversion.